Study on robots failures in automotive painting line - Majid, M.A.A. (Asian Research Publishing Network, 2017)
The increasing number of robots in the automotive industries improved the production throughput, quality and safety. More robots encountered more failures. This paper analyzes the probability of failures of robot at components level in automotive top coat painting line. Timely analysis of failures could reduce the downtime. The objective of this research is to establish replacement strategy for replacement of robots due to components failure. The approaches used in this research are 1) analyzing failures data, mean time between failures (MTBF) and mean time to repair (MTTR), 2) computational of the defender maintenance annual cost and challenger minimum cost of operating. The probability of failures of robots in the top coat system are mainly due to servo motor with a probability of failure is 0.20. From the analysis the robot with lowest MTBF is 5280 hours. Replacement strategy was established using marginal cost (MC) and equivalent uniform annual cost (EUAC) analysis was done for the robot and the potential candidate for replacement. Result from the case study, the cost of maintaining defender at year 6 is Malaysian Ringgit 825,000, while the minimum cost of annual operating of challenger is Malaysian Ringgit 765, 999. It is indicated the cost of the maintaining the defender is higher than the minimum annual operating cost of challenger at year 6. Hence, replacement of defender should be made by end of year 5. © 2006-2017 Asian Research Publishing Network (ARPN). All rights reserved.